Top-down local management, perceived contribution to people, and actual detriments influence a rampant human‒top predator conflict in the Neotropics - Zuluaga Castañeda, Santiago (2022)
In most Neotropical countries the proliferation of illegal firearms, limited funding, and low presence of authorities precludes effective application of top-down governance. Despite that, to our knowledge, top-down governance and top predator detriments or benefits to people (perceived and actual) have never been integrated into an empirical study of human‒top predator conflict. We hypothesize that people's tolerance towards the black-and-chestnut eagle (Spizaetus isidori), a Neotropical top predator, will vary based on the eagle's perceived contributions to people, actual detriments to people, people's support of the top-down local management, and country governance. We tested our hypothesis by carrying out a closed-ended question survey in human communities around 27 eagle nesting sites in two countries (Colombia and Ecuador). People's tolerance towards the eagle showed a negative relationship with perceived detriments, actual detriments, and disapproval of the top-down local management, but there was no influence of country governance. Overall, most people showed high (41.13%) or neutral (35.46%) tolerance towards the eagle and less than a quarter (23.41%) showed low tolerance. Forty percent of people disapproved of the top-down local management. We documented human persecution of this top predator in the majority of sampled nests (59%, 16 of 27) and across all the geographical jurisdictions assessed. Our results suggest that poor governance could also negatively affect other human‒top predator conflicts in the Neotropics. To be more effective at saving top predators in the Neotropical Region, structural changes such as a better balance between bottom-up and top-down approaches and, thus, co-management among stakeholders are needed.